2014
DOI: 10.1039/c3cc49695c
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to glycan targeting: enzyme inhibition by oligosaccharide metalloshielding

Abstract: Metalloglycomics - the effects of defined coordination compounds on oligosaccharides and their structure and function – opens new areas for bioinorganic chemistry and expands its systematic study to the third major class of biomolecules after DNA/RNA and proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 25 publications
(48 reference statements)
2
50
0
2
Order By: Relevance
“…Previous ESI‐MS studies showed that AH44 (6+) and TriplatinNC (8+) protect the sulfate groups of an octasaccharide (DP8) against dissociation through the formation of stable 1:1 adducts . In the present work we used ESI‐MS to study the protection from sulfate loss of 1:1 PPC–FPX adducts in the gas phase (Figure S2).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous ESI‐MS studies showed that AH44 (6+) and TriplatinNC (8+) protect the sulfate groups of an octasaccharide (DP8) against dissociation through the formation of stable 1:1 adducts . In the present work we used ESI‐MS to study the protection from sulfate loss of 1:1 PPC–FPX adducts in the gas phase (Figure S2).…”
Section: Resultsmentioning
confidence: 97%
“…The sulfate residues are the critical recognition features for HS interaction with protein substrates such as growth factors. We have recently shown that sulfate cluster masking, or “metalloshielding”, by clinically relevant anticancer polynuclear platinum complexes (PPCs)—Triplatin (BBR3464) and its substitution‐inert analogue TriplatinNC—is an effective way to protect HS from the actions of its associated enzymes and proteins . By protecting the substrate, the shielding concept is a complementary and attractive alternative to the time‐consuming synthesis of small oligosaccharides, which are generally designed to act as competitive inhibitors toward heparanase .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heparanase inhibition results confirm the previous data from the colorimetric assay using heparinase I, where inhibition was charge-dependent and comparison of a series of compounds also indicated a bond-forming contribution to the activity of Triplatin. 9 The individual coordinating moieties on FPX and by extension the HS backbone – predominantly sulfate oxygen and possibly carboxylate – are inherently weaker ligands for covalent bond formation to Pt compared to those of DNA (N donor atoms of purines and pyrimidines) and proteins (N of histidine and S of cysteine and methionine residues). The aquation kinetics in 15 mM SO 4 2– of a prototypical dinuclear compound structurally analogous to Triplatin, [{ trans -PtCl(NH 3 ) 2 } 2 (μ-NH 2 (CH 2 ) 6 NH 2 )] 2+ , showed a very high k L for loss of sulfate suggesting that, when formed, the sulfate species will be substitution-labile.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically from our own laboratory, non-covalent H-bonding interactions on polynuclear platinum compounds (PPCs) have described the phosphate clamp, a third mode of (ligand)-DNA interaction discrete from the classical minor groove binding and intercalation [1,2]. An unedited mode of cellular accumulation of PPCs identifying HeparanSulfateProteoGlycans (HSPGs) as receptors through initial non-covalent binding to oligosaccharides has significant implications for new target discovery for coordination compounds [3,4]. Stacking π-π interactions play a fundamental role in biology and especially DNA/RNA-protein selective recognition.…”
Section: Introductionmentioning
confidence: 99%